Seroprevalence of Influenza A(H1N1)pdm09 Virus Antibody, England, 2010 and 2011 - Hoschler, Katja (Centers for Disease Control and Prevention, 2012)
The intense influenza activity in England during the 2010–11 winter resulted from a combination of factors. Population-based seroepidemiology confirms that the third wave of influenza A(H1N1)pdm09 virus circulation was associated with a shift in age groups affected, with the highest rate of infection in young adults.